2010
DOI: 10.1021/jp102180q
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Dynamics of 1-Ethyl-3-methylimidazolium Acetate via Molecular Dynamics and Neutron Diffraction

Abstract: The liquid state structure of the ionic liquid, 1-ethyl-3-methylimidazolium acetate ([C(2)mim][OAc]), an excellent nonderivitizing solvent for cellulosic biomass, has been investigated at 323 K by molecular dynamics (MD) simulation and by neutron diffraction using the SANDALS diffractometer at ISIS to provide experimental differential neutron scattering cross sections from H/D isotopically substituted materials. Ion-ion radial distribution functions both calculated from MD and derived from the empirical potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
120
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(139 citation statements)
references
References 35 publications
16
120
2
Order By: Relevance
“…Indeed, molecular dynamics simulations and neutron diffraction studies on 1-ethyl-3-methylimidazolium acetate revealed the liquid structure as inplane interactions of acetate oxygen atoms with the three imidazolium ring hydrogens and cation−cation planar stacking above/below the imidazolium rings. 40 This in-plane organized liquid structure through strong directional hydrogen bonds for the imidazolium-based ILs also supports the intriguing observation of a lower value of viscosity for the [ 39,41 Trying to foster a deeper analysis on this phenomenon, we further carried out mass spectrometry studies. These observations are in fact supported by mass spectrometry data concerning the gas phase fragmentation of isolated [(Cation) 2 Anion] + aggregates induced by collision with a neutral gas (MS/MS).…”
Section: ■ Results and Discussionsupporting
confidence: 72%
“…Indeed, molecular dynamics simulations and neutron diffraction studies on 1-ethyl-3-methylimidazolium acetate revealed the liquid structure as inplane interactions of acetate oxygen atoms with the three imidazolium ring hydrogens and cation−cation planar stacking above/below the imidazolium rings. 40 This in-plane organized liquid structure through strong directional hydrogen bonds for the imidazolium-based ILs also supports the intriguing observation of a lower value of viscosity for the [ 39,41 Trying to foster a deeper analysis on this phenomenon, we further carried out mass spectrometry studies. These observations are in fact supported by mass spectrometry data concerning the gas phase fragmentation of isolated [(Cation) 2 Anion] + aggregates induced by collision with a neutral gas (MS/MS).…”
Section: ■ Results and Discussionsupporting
confidence: 72%
“…The first one considered a trimer of BmimAc. Its initial configuration was built following the structure proposed by neutron scattering experiment for the EmimAc/water mixture [62]. In the second approach, the Monte Carlo computational method [63] was used to obtain the initial configuration of one BmimAc ion pair solvated by water molecules.…”
Section: Methodsmentioning
confidence: 99%
“…The initial configuration of water around BmimAc was obtained from Monte Carlo simulation of one BmimAc in a simulation box of 863 water molecules. In the case of the trimer, the initial configuration is based on the optimized geometry of Emim-Ac[62].…”
mentioning
confidence: 99%
“…63 This is because the existing force field models for ILs overestimate the charges on the ions, thereby leading to increased electrostatic interactions and decreased dynamics. Recently, new force field parameters for ILs based on refined charges have been found to show a good match with experimental data on the structure and dynamics of neat ILs.…”
Section: Ils Inmentioning
confidence: 99%